INDONESIAN EFL LEARNERS’ SELF-EFFICACY TOWARD THEIR LEARNING ACHIEVEMENT - Heri Alfian; Aqzhariady Khartha; Muthmainnah Bahri A. Bohang (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
This study aimed to find out how the self-efficacy impact Indonesian EFL learners’ learning achievement. This study was conducted at Sembilanbelas November University of Kolaka. The subjects were six 7th students of English Education Department. The study was employed a case study design. The instrument used to gather the data was interview guidelines to explore the sources of self-efficacy. Data of interview were analyzed based on procedure of data analysis that consisted of the data condensation, data display, and drawing conclusion/data verification. The results of the study shown that students who have high index achievement have high self-efficacy, judging by their confidence in answering questions and viewed from the sources of self-efficacy students who have high index achievement have high self-efficacy in mastery experiences and physiological states. Students who have middle index achievement have high self-efficacy because they have high confidence in answering questions, and viewed from the source of self-efficacy students who have middle index achievement have high self-efficacy in vicarious experiences and physiological states. Students who have low index achievement have low self-efficacy because they do not have high confidence in their ability to answer questions. So, students who have low index achievement have low self-efficacy in mastery experiences and physiological states. Based on the findings, the researcher recommends that it is important to the students to identify their self-efficacy because self-efficacy is essential for learners to facing the problems in academic colleges. Also, students with high levels of academic self-efficacy are more likely to persist at challenging academic tasks and put effort to achieve success in academic college, while students with low self-efficacy tend to give up easily and not confident of being able to perform given assignment